Insights Into Thiamine Supplementation in Patients With Septic Shock - Costa, Nara Aline; Pereira, Amanda Gomes; Sugizaki, Clara Sandra Araujo; Vieira, Nayane Maria; Garcia, Leonardo Rufino; Paiva, Sérgio Alberto Rupp de; Zornoff, Leonardo Antonio Mamede; Azevedo, Paula Schmidt; Polegato, Bertha Furlan; Minicucci, Marcos Ferreira (Frontiers in Medicine, 2022)
Septic shock is associated with unacceptably high mortality rates, mainly in developing countries. New adjunctive therapies have been explored to reduce global mortality related to sepsis. Considering that metabolic changes, mitochondrial dysfunction and increased oxidative stress are specific disorders within the path of septic shock, several micronutrients that could act in cellular homeostasis have been studied in recent decades. Thiamine, also known as vitamin B1, plays critical roles in several biological processes, including the metabolism of glucose, synthesis of nucleic acids and reduction of oxidative stress. Thiamine deficiency could affect up to 70% of critically ill patients, and thiamine supplementation appears to increase lactate clearance and decrease the vasopressor dose. However, there is no evident improvement in the survival of septic patients. Other micronutrients such as vitamin C and D, selenium and zinc have been tested in the same context but have not been shown to improve the outcomes of these patients. Some problems related to the neutrality of these clinical trials are the study design, doses, route, timing, length of intervention and the choice of endpoints. Recently, the concept that multi-micronutrient administration may be better than single-micronutrient administration has gained strength. In general, clinical trials consider the administration of a single micronutrient as a drug. However, the antioxidant defence is a complex system of endogenous agents in which micronutrients act as cofactors, and the physiological interactions between micronutrients are little discussed. In this context, the association of thiamine, vitamin C and corticoids was tested as an adjunctive therapy in septic shock resulting in a significant decrease in mortality. However, after these initial results, no other study conducted with this combination could reproduce those benefits. In addition, the use of low-dose corticosteroids is recommended in patients with septic shock who do not respond to vasopressors, which can affect the action of thiamine. Therefore, given the excellent safety profile, good biologic rationale and promising clinical studies, this review aims to discuss the mechanisms behind and the evidence for single or combined thiamine supplementation improving the prognosis of patients with septic shock.